Synthesis and biological evaluation of triterpenoid thiazoles derived from betulonic acid, dihydrobetulonic acid, and ursonic acid - Borková, Lucie; Frydrych, Ivo; Jakubcová, Nikola; Adámek, Richard; Lišková, Barbora; Gurská, Soňa; Medvedíková, Martina; Hajdúch, Marián; Urban, Milan (European journal of medicinal chemistry, 2020)
In this work, 35 new derivatives of betulonic, dihydrobetulonic and ursonic acid were prepared including 30 aminothiazoles and all of them were tested for their in vitro cytotoxic activity in eight cancer cell lines and two non-cancer fibroblasts. Compounds with the IC50 below 5 μM in CCRF-CEM cells and low toxicity in non-cancer fibroblasts (4m, 5c, 5m, 6c, 6m, 7b, and 7c) were further subjected to tests of pharmacological parameters yielding the final set for advanced biological evaluation (4m, 5m, 6m, and 7b). It was proved by several methods, that all of them trigger apoptosis via the intrinsic pathway and derivatives 5m and 7b are the most effective (IC50 2.4 μM and 3.6 μM). They are the best candidates to become potentially new anticancer drugs and will be subjected to in vivo tests in mice. In addition, compounds 6b and 6c deserve more attention because their activity is not limited only to chemosensitive CCRF-CEM cell line. Specifically, compound 6b is highly active against K562 leukemic cell line (0.7 μM) and its IC50 activity in colon cancer HCT116 cell line is 1.0 μM. Compound 6c is active in both normal K562 and resistant K562-TAX cell lines (IC50 3.4 μM and 5.4 μM) and both colon cancer cell lines (HCT116 and HCT116p53-/-, IC50 3.5 μM and 3.4 μM).
Keywords: vztahy mezi strukturou a aktivitou; Oleanolic Acid; Cells, Cultured; Cell Proliferation; Humans; Caspase assay; Structure-Activity Relationship; Molecular Structure; mikrozomy; Microsomes; Antineoplastic Agents; Membrane Potential, Mitochondrial; Cytotoxicity; Triterpenes; protinádorové látky; Thiazole; Drug Screening Assays, Antitumor; apoptóza; screeningové testy protinádorových léčiv; membránový potenciál mitochondrií; thiazoly; Biological activity; proliferace buněk; terpeny; Terpenes; triterpeny; Cancer; kultivované buňky; Dose-Response Relationship, Drug; vztah mezi dávkou a účinkem léčiva; Triterpene; lidé; Heterocycle; Thiazoles; fibroblasty; Fibroblasts; kyselina olenalová; Apoptosis; molekulární struktura